Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.34001/edulingua.v7i2.1392
|View full text |Cite
|
Sign up to set email alerts
|

Enterpreneurial-Based English Learning (Miss Maya) to Build Entrepreneurial Leadership for Students College

Abstract: The industrial revolution is a fusion of automation technology with cyber. The current trend in the industrial world is starting to touch the virtual world with several systems such as cyber physical systems, internet of things (IoT), cloud computing, and cognitive computing. Revolution 4.0 implements intelligent technology that can be connected to various lines of life, including students’ needs. They must be active to form their entrepreneurial leadership to face these challenges. Absolutely, this must be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this study, the writer applied a descriptive mixed method that described, identified, classified, and calculated numerical data on the words of affixes found in Kahlil Gibran's poetry. According to Heriyanto and Khudlori (2020) explained that "Primary data include references/ literature/ journals/ books related to the discussion. Secondary data include documentation and field data of the implementation obtained through observation and interviews" (p.41).…”
Section: Types Of Research Methodsmentioning
confidence: 99%
“…In this study, the writer applied a descriptive mixed method that described, identified, classified, and calculated numerical data on the words of affixes found in Kahlil Gibran's poetry. According to Heriyanto and Khudlori (2020) explained that "Primary data include references/ literature/ journals/ books related to the discussion. Secondary data include documentation and field data of the implementation obtained through observation and interviews" (p.41).…”
Section: Types Of Research Methodsmentioning
confidence: 99%